Analisis Pengaruh Profitabilitas, Pertumbuhan Penjualan dan Likuiditas terhadap Struktur Modal pada Perusahaan Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019 - Muhammad Zulfikar Fahri Pratama; Muhammad Roni Indarto (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2021)
The prospect of growth in the consumer goods industry sector tends to increase from year to year, attracting the attention of investors to invest their money in companies in the consumer goods industry sector. This can happen because the consumption of people’s daily needs also increases every year. However, in investing, investors must also pay attention to the financial health condition of a company. In general, the financial condition of a healthy company can be seen from its capital structure. The company’s capital structure in several studies conducted is influenced by profitability, sales growth and liquidity, the effect of the three variables on the capital structure varies, there is a significant negative or insignificant negative effect, there is even a significant positive effect. In this study, there is a negative and significant influence between Profitability and Capital Structure, there is a negative and insignificant effect between Sales Growth and Capital Structure, and there is a negative and significant effect between Liquidity and Capital Structure in Consumer Goods Industrial Sector companies listed on the Indonesia Stock Exchange in 2017 -2019.